Model Pembelajaran Bagi Anak Berkebutuhan Khusus Tuna Wicara di SLBN 1 Kulon Progo - Noer Hanifah Lestari; Deti Novianti; Fahmi Zen; Difa’ul Husna (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The purpose of this research is to find out what learning models are carried out by the teacher of the speech impaired in carrying out the teaching and learning process of the dıdık participants where the scope is the dıdık participants and the teacher of the speech impaired The method used is the qualitative method through observations and interviews located at SLBN 1 Kulon Progo with two respondents, namely the teacher of the speech impaired at SLBN 1 Kulon Progo. The results showed that SLBN 1 Kulon Progo uses several ways in carrying out the teaching and learning process, namely by using several methods such as the demonstration method, everyone is teacher here method, the existence of technology or media used such as whiteboards, computers, and others, as well as the existence of inhibiting factors and supporting factors and the involvement of parents.